Mycobacteria exploit nitric oxide‐induced transformation of macrophages into permissive giant cells. (5th December 2018) - Gharun, Kourosh; Senges, Julia; Seidl, Maximilian; Lösslein, Anne; Kolter, Julia; Lohrmann, Florens; Fliegauf, Manfred; Elgizouli, Magdeldin; Alber, Marco; Vavra, Martina; Schachtrup, Kristina; Illert, Anna L; et al.
Abstract :